Irregularity as a unifying principle of the novel trilogy by Stanislav Komárek - Antoš, Matěj (Bohemica Olomucensia, 2020)
The study focuses on the works of prose by contemporary Czech philosopher, biologist and essayist Stanislav Komarek, specifically on three novels, sometimes referred to as "irregular trilogy": Opšlstisova nadace (Opšlstis Foundation, 2002), Černý domeček (Black House, 2004) and Mandaríni (Mandarins, 2007). With the use of analytical-interpretive probes the study aims to find out and prove whether the principle of irregularity itself might work as a connecting link between the texts on different levels, especially regarding the genre structure, fictional setting and the way how aluctions and mystifications are utilized within the texts.
Keywords: Stanislav Komárek; irregular trilogy; contemporary Czech prose; literary analysis; postmodern literature